9y-6x=3+5x

Simple and best practice solution for 9y-6x=3+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-6x=3+5x equation:


Simplifying
9y + -6x = 3 + 5x

Reorder the terms:
-6x + 9y = 3 + 5x

Solving
-6x + 9y = 3 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-6x + -5x + 9y = 3 + 5x + -5x

Combine like terms: -6x + -5x = -11x
-11x + 9y = 3 + 5x + -5x

Combine like terms: 5x + -5x = 0
-11x + 9y = 3 + 0
-11x + 9y = 3

Add '-9y' to each side of the equation.
-11x + 9y + -9y = 3 + -9y

Combine like terms: 9y + -9y = 0
-11x + 0 = 3 + -9y
-11x = 3 + -9y

Divide each side by '-11'.
x = -0.2727272727 + 0.8181818182y

Simplifying
x = -0.2727272727 + 0.8181818182y

See similar equations:

| 7s-(3s+1)=4(s+s) | | -2(n-5)+4n=17 | | -(-x+w)-2(-4w+5x)= | | F(x)=4x+10F(2) | | sqrt(3x+1)-sqrt(x-1)=2 | | 4a+3=7a-16 | | 80=11c+32 | | 1/2+(2/3/3/4)-4/5*5/6= | | 4y-8-3y=2y-12 | | 8x+7=12-2x | | 17x-3+17x+8= | | 66=-3(3n-4) | | 3x^4-30x^2+27= | | 3x+10=x+29 | | 7.06=.36x+(35.3+-1.85x) | | 3n-8=52 | | 3n-8=53 | | 22-d=17 | | 6x+5=-36+4x | | -3u+1+7w=4w+4-5 | | 51-(-6)=-4x+12-x | | 24a-22=4(6a-1) | | 4n-8=-24 | | 16=1.8+32 | | 7.06=.37x+.20a | | (8-2)+24*12= | | 45x-16x^2=10 | | 2x^2+4xy+2y^2-5x+4y+7=0 | | 4x-B(x+1)(x+1)+4x=4-Bx^2 | | -6x-6+8x=2x-6 | | 17-7=-32 | | 75c^2+90cd+27d^2=0 |

Equations solver categories